Free and pedicled flaps for reconstruction of the weightbearing sole of the foot: a comparative analysis of functional results - Struckmann, Victoria; Hirche, Christoph; Struckmann, Folkart; Harhaus-Wähner, Leila; Lehnhardt, Marcus; Kneser, Ulrich; Daigeler, Adrien (The journal of foot and ankle surgery, 2014)
Reconstruction of the weightbearing sole of the foot is complex and requires soft tissue that is resistant to weight, pressure, and shear stress. Despite a variety of flap types and techniques, it is still challenging to meet these demands. The present retrospective study included 21 patients after reconstruction of plantar tissue defects from 2001 to 2011. The outcome was evaluated using the lower extremity functional scale, Weber score, pedobarography, assessment of shifting, and sensory recovery. The patients' quality of life was documented using the SF-36 questionnaire. Plantar reconstruction was performed using 12 free and 9 pedicled flaps. No differences in functional results were observed between the flap types, despite a better sense of temperature in the adipocutaneous flaps. The extent of flap shifting was independent of the flap type and did not correlate with the functional results. Pedobarography showed a tendency for increased peak pressure and prolonged contact time in the reconstructed weightbearing plantar areas compared with the sound feet and a control group. The present study found no relevant differences in the functional results between different flap types and free or pedicled techniques. Flap selection should be based on the individual requirements and availability of donor sites.